Watershed Management and Livelihoods: Lessons from Nepal (Journal of Forest and Livelihood, 2009)
Watershed management is a holistic approach to managing watershed resources that integrates forestry, agriculture, pasture and water management, with an objective of sustainable management of natural resources. This approach seeks to promote interactions among multiple stakeholders within and between the upstream and downstream locations of a watershed. The experiences from Nepal suggest that these ideals of watershed management do not appear to be strongly linked with the current policies, programmes and practices. A mechanism for constant dialogue between policymakers, practitioners and communities at landscape level would help in linking the upstream and downstream ecology to improve the livelihoods of the local people and sustainable watershed resource management.Key words: watershed management, upstream and downstream, conservation and livelihoods  Full text is available at the ForestAction websiteJournal of Forest and Livelihood 6(2) September 2007 pp.67-75